THE IMPACT OF NORMALIZATION PROCEDURES ON THE CLASSIFICATION OF BUILDING MATERIALS COMPANIES LISTED ON THE WARSAW STOCK EXCHANGE (Polityki Europejskie, Finanse i Marketing)
One of the stages of the comparative analysis of multivariate objects is the data normalization. There are many procedures of the normalization of the variables described in the literature. The choice of the normalization method is one of the most crucial steps for the researchers as it has a profound effect on the results of the analysis. The main goal of the present study is to examine the sensitivity of the result of linear ordering of objects, using three selected normalization methods, in calculating a synthetic taxonomic measure TMAI to create ratings of 15 building materials companies, listed on the Warsaw Stock Exchange. The study was made for the years 2013 and 2014. The conducted study shows that the use of different normalization formulas of variables can cause the change of the results of the companies classification, which does not result neither from the data structure change nor the effectiveness modification of their operations.